Occurrence of Cryptosporidium (Apicomplexa, Cryptosporidiidae) in Crotalus durissus terrificus (Serpentes, Viperidae) in Brazil - Karasawa, Andréa Satie Matsubara [UNESP]; Silva, Reinaldo José da [UNESP]; Mascarini, Luciene Maura [UNESP]; Barrella, Thomaz Henrique [UNESP]; Lopes, Carlos Alberto de Magalhães [UNESP] (Instituto Oswaldo Cruz, Ministério da Saúde, 2002)
The objective of the present study was to investigate the prevalence of Cryptosporidium (Apicomplexa, Cryptosporidiidae) in the snake Crotalus durissus terrificus (Serpentes, Viperidae). Fifty animals were evaluated for the presence of oocysts of Cryptosporidium sp. at the time of arrival and 30 and 60 days later. Intestinal washings with saline solution (1% body weight), fecal samples, and organ scrapings were collected during the study. Oocysts were concentrated by an ether-phosphate-buffered saline sedimentation technique and then separated by a density gradient centrifugation technique. Smears were made with the sediment and submitted to modified acid-fast and auramine-rhodamine staining. Cryptosporidium-positive smears were used as controls for the experimental findings. The overall prevalence of Cryptosporidium sp. oocysts was 14%. Among the positive snakes, oocysts were detected only in the intestinal washing in two specimens, only in the feces in four specimens, and in both materials at least once in one specimen. The positive snakes were predominantly from Santa Maria da Serra city State of São Paulo (57.1%). We also observed that all of the examinations that presented positive results were obtained at least 27 days after the capture of the animals.
Keywords: Cryptosporidium; Crotalus durissus terrificus; snakes; Brazil